Granulomas in Diagnostic Biopsies Associated With High Risk of Crohn's Complications—But May Be Preventable. Issue 4 (30th April 2022) - Lawrence, Lindsey S; Heider, Amer; Singer, Andrew A M; Neef, Haley C; Adler, Jeremy
Abstract: Background: Granulomatous intestinal inflammation may be associated with aggressive Crohn's disease (CD) behavior. However, this has not been confirmed, and it is unknown if associated disease complications are preventable. Methods: This is a retrospective cohort of patients younger than 21 years at CD diagnosis (November 1, 2005 to November 11, 2015). Clinical information was abstracted, including dates of starting medications and the timing of perianal fistula or stricture development, if any. Diagnostic pathology reports were reviewed, and a subset of biopsy slides were evaluated by a blinded pathologist. Patients were excluded if perianal fistula or stricture developed within 30 days after CD diagnosis. Medications were included in analyses only if started >90 days before development of perianal fistula or stricture. Results: In total, 198 patients were included. Half (54%) had granulomas at diagnosis. Granulomas were associated with a greater than 3-fold increased risk of perianal fistula (hazard ration [HR] = 3.24; 95% confidence interval CI], 1.40–7.48). Immunomodulator and anti-tumor necrosis factor-α (anti-TNF) therapy were associated with 90% (HR, = 0.10; 95% CI, 0.03–0.42) and 98% (HR, = 0.02; 95% CI, 0.01–0.10) reduced risk of perianal fistula, respectively. Patients with granulomatous inflammation preferentially responded to anti-TNF therapy with reduced risk of perianal fistula. The presence of granulomas was not associated with risk of stricture. Immunomodulator and anti-TNF therapy were associated with 96% (HR, = 0.04; 95% CI, 0.01–0.22) and 94% (HR, = 0.06; 95% CI, 0.02–0.20) reduced risk of stricture, respectively. Conclusions: Granulomas are associated with increased risk of perianal fistula but not stricture. Steroid sparing therapies seem to reduce the risk of both perianal fistula and stricture. For those with granulomas, anti-TNF-α therapy greatly reduced the risk of perianal fistula development, whereas immunomodulators did not.